Health‐related quality of life in patients with relapsed/refractory multiple myeloma treated with pomalidomide and dexamethasone ± subcutaneous daratumumab: Patient‐reported outcomes from the APOLLO trial. Issue 4 (6th February 2022) - Terpos, Evangelos; Dimopoulos, Meletios A.; Boccadoro, Mario; Delimpasi, Sosana; Beksac, Meral; Katodritou, Eirini; Moreau, Philippe; Pompa, Alessandra; Symeonidis, Argiris; Bila, Jelena; Oriol, Albert; Mateos, Maria‐Victoria; et al.
Abstract: In the phase 3 APOLLO trial, daratumumab in combination with pomalidomide and dexamethasone (D‐Pd) significantly reduced the rate of disease progression or death by 37% relative to Pd alone in patients with relapsed/refractory multiple myeloma (RRMM) who had received ≥1 prior line of therapy including lenalidomide and a proteasome inhibitor. Here, we present patient‐reported outcomes (PROs) from APOLLO. Median treatment duration was 11.5 months with D‐Pd and 6.6 months with Pd. PRO compliance rates were high and similar in both groups. No changes from baseline were observed for EORTC QLQ‐C30 global health status scores in either group, while physical and emotional functioning, disease symptoms, and adverse effects of treatment remained at baseline levels with D‐Pd but worsened with Pd. Reductions ( p  < 0.05) in pain and fatigue were seen at several time points with D‐Pd versus Pd. Overall, these results suggest patients' health‐related quality of life remained stable when daratumumab was added to Pd, with several results favoring D‐Pd versus Pd. These findings complement the significant clinical improvements observed with D‐Pd and support its use in patients with RRMM.